Neighborhood environment, social participation, and physical activity in older adults with lower limb osteoarthritis: a mediation analysis - Herbolsheimer, Florian; Ungar, Nadine; Portegijs, Erja; Dallmeier, Dhayana; Schaap, Laura; Smith, Toby; Stubbs, Brendon; Deeg, Dorly; Peter, Richard; Castell, Maria Victoria; Otero, Ángel; Edwards, Mark; et al. (Health & place, 2021)
Older adults with lower limb osteoarthritis (LLOA) are highly dependent on their physical and social environment for being physically active. Longitudinal data from 2286 older adults (Mage = 73.8 years; 50.3% female) in six European countries were analyzed using cross-lagged Structural Equation Modeling (SEM) and multi-group SEM. In cross-sectional analyses, neighborhood resources were associated with physical activity (r = 0.26;p < .001) and social participation (r = 0.13;p = .003). Physical activity at follow-up was associated with neighborhood resources, with this relationship mediated by social participation in people with LLOA (β = 0.018;p = .013). To promote future physical activity, opportunities to socially engage in neighborhoods need to be targeted primarily to people with LLOA.
Gesehen am 12.05.2021